1986
DOI: 10.1002/j.1460-2075.1986.tb04194.x
|View full text |Cite
|
Sign up to set email alerts
|

Endonuclease VII resolves Y-junctions in branched DNA in vitro.

Abstract: Endonuclease VII (gp 49 of phage T4) resolves four‐way junctions in branched DNAs. We have extended our investigations of the specificity of endo VII and tested its activity with three‐way junctions (Y‐structures) constructed in vitro. Both ‘closed’ and ‘open’ Y‐structures were made, absolutely identical in sequence but differing from each other by a single nick in one of the three arms. Pure Y‐structures were obtained on a preparative scale by annealing plus and minus strands from two M13mp strains. One strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 33 publications
4
51
0
Order By: Relevance
“…These include, among others, three-way junctions (Y structures) such as occur at the replication fork during DNA replication. Endo VII has been shown to resolve a variety of synthetically constructed Y structures into linear molecules by introducing nicks 3Ј to the junction (15,33). To our knowledge, however, endo VII cleavage of naturally occurring RIs has not been investigated so far.…”
Section: Resultsmentioning
confidence: 99%
“…These include, among others, three-way junctions (Y structures) such as occur at the replication fork during DNA replication. Endo VII has been shown to resolve a variety of synthetically constructed Y structures into linear molecules by introducing nicks 3Ј to the junction (15,33). To our knowledge, however, endo VII cleavage of naturally occurring RIs has not been investigated so far.…”
Section: Resultsmentioning
confidence: 99%
“…This decrease is consistent with EndoVII-mediated cleavage of the regressed fork Holliday junction. However, previous reports have suggested that EndoVII also cleaves Y-shaped molecules, such as the origin fork, in vivo (14,15). Direct cleavage of the origin fork junction by EndoVII would decrease the number of origin forks available for regression, indirectly decreasing the accumulation of regressed origin forks.…”
Section: Accumulation and Resolution Of Origin Forks In Various Mutantmentioning
confidence: 95%
“…The major function of EndoVII appears to be the resolution of branched molecules before packaging of DNA into phage heads. In contrast to some other resolvases, such as RuvC, EndoVII can act on a broad range of DNA structures in vitro, including fork-shaped structures (14)(15)(16).…”
mentioning
confidence: 99%
“…This enzyme also cleaves synthetic Y structures composed of three complementary oligonucleotides (46,47), suggesting that it could play a role in the processing of blocked replication forks in vivo. To begin to test this hypothesis, we compared blocked forks induced by m-AMSA in T4 wild-type versus T4 gene 49 amber-mutant (T4 49 am ) infections of a nonsuppressing host.…”
Section: Accumulation Of Blocked Replication Forks In Gene 49mentioning
confidence: 99%